The effect of lower hybrid waves on JET plasma rotation. (22nd December 2016) - Nave, M.F.F.; Kirov, K.; Bernardo, J.; Brix, M.; Ferreira, J.; Giroud, C.; Hawkes, N.; Hellsten, T.; Jonsson, T.; Mailloux, J.; Ongena, J.; Parra, F.
Abstract: This paper reports on observations of rotation in JET plasmas with lower hybrid current drive. Lower hybrid (LH) has a clear impact on rotation. The changes in core rotation can be either in the co- or counter-current directions. Experimental features that could determine the direction of rotation were investigated. Changes from co- to counter-rotation as the q -profile evolves from above unity to below unity suggests that magnetic shear could be important. However, LH can drive either co- or counter-rotation in discharges with similar magnetic shear and at the same plasma current. It is not clear if a slightly lower density is significant. A power scan at fixed density, shows a lower hybrid power threshold around 3 MW. For smaller LH powers, counter rotation increases with power, while for larger powers a trend towards co-rotation is found. The estimated counter-torque from the LH waves, would not explain the observed angular frequencies, neither would it explain the observation of co-rotation.